MOLECULAR ANALYSIS AND MODELING OF INACTIVATION OF HUMAN CYP2D6 BY FOUR MECHANISM BASED INACTIVATORS - Livezey, Mara (2012)
Human cytochrome P450 2D6 (CYP2D6) is involved in metabolism of approximately 25% of pharmaceutical drugs. Inactivation of CYP2D6 can lead to adverse drug interactions. Four inactivators of CYP2D6 have previously been identified: 5-Fluoro-2-[4-[(2-phenyl-1H-imidazol-5-yl)methyl]-1-piperazinyl]pyrimidine (SCH66712), (1-[(2-ethyl-4-methyl-1H(-EMTPP-imidazol-5-yl)-methyl]-4-[4-(trifluoromethyl)-2-pyridinyl]piperazine (EMTPP), paroxetine, and 3,4-methylenedioxymethamphetamine (MDMA). All four contain planar, aromatic groups as well as basic nitrogens common to CYP2D6 substrates. SCH66712 and EMTPP also contain piperazine groups and substituted imidazole rings that are common in pharmaceutical agents, though neither of these compounds is clinically relevant. Paroxetine and MDMA contain methylenedioxyphenyls. SCH66712 and EMTPP are both known protein adductors while paroxetine and MDMA are probable heme modifiers. The current study shows that each inactivator displays Type I binding with K(s) values that vary by 2-orders of magnitude with lower K(s) values associated with greater inactivation. Comparison of K(I), k(inact), and partition ratio values shows SCH66712 is the most potent inactivator. Molecular modeling experiments using AutoDock identify Phe120 as a key interaction for all four inactivators with face-to-face and edge-to-face pi interactions apparent. Distance between the ligand and heme iron correlates with potency of inhibition. Ligand conformations were scored according to their binding energies as calculated by AutoDock and correlation was observed between molecular models and K(s) values.